2018
DOI: 10.1128/aem.01125-18
|View full text |Cite
|
Sign up to set email alerts
|

Response of Secondary Metabolism of Hypogean Actinobacterial Genera to Chemical and Biological Stimuli

Abstract: Microorganisms within microbial communities respond to environmental challenges by producing biologically active secondary metabolites, yet the majority of these small molecules remain unidentified. We have previously demonstrated that secondary metabolite biosynthesis in actinomycetes can be activated by model environmental chemical and biological stimuli, and metabolites can be identified by comparative metabolomics analyses between stimuli conditions. Herein, we survey the secondary metabolite productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Moreover, isolation media that mimic the conditions of low concentration nutrients in caves such as tap water agar, 1/100 ISP2 and oligotrophic medium (M5) were also successfully used for the isolation of actinobacteria. (Lee et al, 2000b; Velikonja et al, 2014; Covington et al, 2018; Passari et al, 2018). High concentration of nutrients in standard cultivation media were reported to cause cell death in cave-associated bacteria due to osmotic stress (Barton, 2006; Ghosh et al, 2017).…”
Section: Selective Isolation Of Cave Actinobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, isolation media that mimic the conditions of low concentration nutrients in caves such as tap water agar, 1/100 ISP2 and oligotrophic medium (M5) were also successfully used for the isolation of actinobacteria. (Lee et al, 2000b; Velikonja et al, 2014; Covington et al, 2018; Passari et al, 2018). High concentration of nutrients in standard cultivation media were reported to cause cell death in cave-associated bacteria due to osmotic stress (Barton, 2006; Ghosh et al, 2017).…”
Section: Selective Isolation Of Cave Actinobacteriamentioning
confidence: 99%
“…Therefore, the second challenge lies in our ability to activate these silent gene clusters. Recently, specific biological and chemical stimuli namely exposure to antibiotics, metals and mixed microbial culture, were successfully employed to activate secondary metabolites production in cave actinobacteria (Covington et al, 2018). Evidently, the study on cave actinobacteria and their bioactive compounds is still at an early stage.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Limestone-rich areas mainly dominated by a CaCO 3 environment, are under-explored ecological niches for mining of microorganisms for various metabolic properties. Recent studies have revealed that both hypogean and epigean limestone actinobacteria are potential antibiotics producers [8][9][10][11][12][13][14] . The state of Meghalaya located in the north-eastern part of India falls under the Indo-Burma Biodiversity Hotspot 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, only the genomes of the isolate and the type strains of S. iranensis , S. violaceusniger and S. rapamycinicus contained bioclusters considered to express for meilingmycin, an anti-parasitic macrolide (Sun et al 2002 ) and nigericin, which inhibits Gram-positive bacteria (Graven et al 1966 ). Similarly, the draft genomes of the isolate, S. albiflaviniger DSM 41598 T and S. javensis DSM 41764 T contained bioclusters predicted to encode for the synthesis of cahuitamycins A-C, which inhibit the formation of bacterial biofilms (Park et al 2016 ), pladienolides, anti-tumour antibiotics (Mizui et al 2004 ) and funisamine, an aminopolyol polyketide antibiotic which inhibits the growth of wild type strains of Staphylococcus aureus , Escherichia coli and Candida albicans (Covington et al 2018 ), respectively. Bioclusters predicted to encode for rapamycin were only detected in the genomes of the S. iranensis and S. rapamycinicus strains.…”
Section: Resultsmentioning
confidence: 99%